Latency of epileptic and psychogenic nonepileptic seizures - Hulya Ozkan; Meliha Turksever; Baburhan Guldiken; Necdet Sut (Arquivos de Neuro-Psiquiatria)
Background Due to their semiological similarities, psychogenic nonepileptic seizures (PNESs) can occasionally hardly be differentiated from epileptic seizures (ESs), and long-term video-electroencephalographic monitoring (VEM) is needed for the differential diagnosis.